The Impact Of Bullwhip Effect Inventory Level And Information Sharing On Retailer Operational Perfomance Mediated By Supply Chain Performance - Cindy Cindy; Immanuel Zai (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of bullwhip effect, inventory levels, and information sharing practices on the performance of supply chains and retailer operations in Batam City. The data was collected through a questionnaire and processed the data using a quantitative data method for 220 respondents who are retail supply chain staff in Batam. Data analysis shows that inventory levels and information-sharing practices have a positive and significant influence on supply chain performance and retailer operations, while the bullwhip effect does not show a significant impact on either aspect. The study emphasizes the need to focus on inventory management strategies and improve information collaboration in the supply chain to improve retailers' operational efficiency.